2013
DOI: 10.1590/s1679-62252013005000001
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between morphology, diet and spatial distribution: testing the effects of intra and interspecific morphological variations on the patterns of resource use in two Neotropical Cichlids

Abstract: Considering the morphology, diet and spatial distribution of Satanoperca pappaterra and Crenicichla britskii (Perciformes: Cichlidae) in the Upper Paraná River floodplain (Brazil), the following questions were investigated: (1) Could the body shape predict the use of trophic resources and habitat by C. britskii and S. pappaterra? (2) Could the relationship between morphology and use of trophic resources and habitat be also extended to the intraspecific scale? (3) What are the most important morphological trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 45 publications
(74 reference statements)
0
36
0
Order By: Relevance
“…Thus, the utilization of indices minimize the chances of the analysis be dominated by a single variable (Winemiller, 1991). Studies using indices were performed by other authors (Gatz, 1979;Watson & Balon, 1984;Montaña & Winemiller, 2010;Sampaio et al, 2013). Higher values indicate lateral compression of the fish, expected for fish that exploit habitats with slower water velocity (Gatz, 1979;Watson & Balon, 1984 Lower values indicate species with depressed bodies, expected for fish that exploit habitats with rapid water velocity (Watson & Balon, 1984;Oliveira, 2005) 3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the utilization of indices minimize the chances of the analysis be dominated by a single variable (Winemiller, 1991). Studies using indices were performed by other authors (Gatz, 1979;Watson & Balon, 1984;Montaña & Winemiller, 2010;Sampaio et al, 2013). Higher values indicate lateral compression of the fish, expected for fish that exploit habitats with slower water velocity (Gatz, 1979;Watson & Balon, 1984 Lower values indicate species with depressed bodies, expected for fish that exploit habitats with rapid water velocity (Watson & Balon, 1984;Oliveira, 2005) 3.…”
Section: Methodsmentioning
confidence: 99%
“…The main goal of ecomorphology is to understand the response of organisms to environmental challenges, by comparing patterns of variations in morphological and ecological characters (Motta et al, 1995). Ecomorphological analysis can be used to describe patterns along niche dimensions, since the body shape provides relevant information about the use of resources by organisms (Bourke et al, 1997;Fugi et al, 2001;Pagotto et al, 2009Pagotto et al, , 2011Oliveira et al, 2010;Sampaio et al, 2013). For example: the depressed and elongated body of armored catfishes (Siluriformes: Loricariidae) permits a more efficient occupation of the bottom in lotic habitats, since this adaptation compensates the difficulties caused by the current, eliminating the effect of drag forces that tend to elevate their body .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the ecomorphological paradigm, intraspecific morphological variations can result in subtle niche differences among the individuals, favoring the adaptation of some fish species according to changes in environmental conditions. These ideas are supported by studies conducted by Mittelbach et al (1992), Robinson et al (1993), Langerhans et al (2003), and Sampaio et al (2013).…”
mentioning
confidence: 62%
“…Thus, investigations on the relationship of the phenotype of a species to its use of the habitat can identify ecomorphological similarities between phylogenetically distant species (Chalcraft & Resetarits Jr., 2003;Oliveira et al, 2010), or establish ecomorphological differences among closely related species (Winemmiler et al, 1995;Wainwright et al, 2002). Many fish, including representatives of the same family (Kassan et al, 2003;Sampaio et al, 2013) or the same genus (Russo et al, 2004;Balassa et al, 2004;Corrêa et al, 2009), may have different feeding habits and associated divergence in their feeding structures. Studies have also shown that the morphology and feeding habits vary, even among individuals of the same species that occupy different environments (Meyer, 1990;Turigan et al, 1995).…”
Section: Introductionmentioning
confidence: 99%